DC UPS for Critical Loads - Ganesh S; Chiranjit Ghosh T; Kokilasree R; Nandhakumar M; Md Haroon Alim T (Institute of Advanced Engineering and Science, 2015)
The usual way to avoid a computer shutdown during a mains failure is to connect an uninterruptible power supply system (UPS), which can be suitably modified and fitted inside the computer cabinet by the use of proposed methodology known as a dc UPS. Conventional desk top UPS systems store electricity in form of chemical energy in batteries and when ever mains fail the batteries provide DC power which is then converter to ac by inverter and then fed to the computer in order to save critical data. Thus power from mains or from UPS is fed to switched mode power supply unit which converts it to dc to supply the computer motherboard and accessories. Leaving the case of the computer powered by mains, duing power failure the dc power is unnecessarily converted to ac and then to dc again in SMPS hence high switching losses and heat is produced there by making the entire system very lowe efficient. In this work it is proposed to directly feed the dc power from the battery to the computer SMPS system by building a UPS arrangement within the computer system. This not noly saves space, it is highly efficient compared to the conventional ups system, easy to carry, low cost and reliable since there is no change over operation is required/. A complete design of an ac to dc power supply with an internal dc UPS is presented in this paper. . A prototype has been fully developed and tested as a PC power supply. Thus the result is achieved at full power about 6-8 minutes.